2000
DOI: 10.1017/s0305741000014612
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Agency and Public Opinion in Guangzhou: The Limits of a Popular Approach to Environmental Governance

Abstract: Researchers on China's environmental governance have usually maintained that the inferior bureaucratic status of the State Environmental Protection Administration (SEPA) (formerly the National Environmental Protection Agency) and its local agencies have accounted for the limited enforcement of environmental regulations in China. Environmental agencies at all levels have found it difficult to obtain active support and co-operation from other bureaucratic authorities in charge of economic development to take a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 23 publications
3
72
1
1
Order By: Relevance
“…To win the support of the public and local people's congress, the GEPB has made substantial efforts to propagate environmental values, arouse popular concerns concerning local environmental problems, handle pollution complaints, and convey people's grievances about environmental concerns to the municipal government. Unfortunately, strong bureaucratic resistance to greater involvement by the public in environmental governance persists inside Guangzhou's bureaucracy (Lo and Leung, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To win the support of the public and local people's congress, the GEPB has made substantial efforts to propagate environmental values, arouse popular concerns concerning local environmental problems, handle pollution complaints, and convey people's grievances about environmental concerns to the municipal government. Unfortunately, strong bureaucratic resistance to greater involvement by the public in environmental governance persists inside Guangzhou's bureaucracy (Lo and Leung, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that the press in coastal cities are relatively more open than in other areas of the country; for example, local newspapers in Shanghai and Guangzhou (Lo and Yip, 1999;Lo and Leung, 2000) have been particularly aggressive in disclosing serious cases of environmental violations. In addition, EPBs have begun to publish annual reports of their work in an effort to draw popular attention to pollution problems (Lo and Leung, 2000). Thus, the degree to which the public is informed about environmental problems, although uneven, has generally increased, as has the importance of public support for environmental protection.…”
Section: H1a: the Enforcement Style Dimensions Of Prioritization And mentioning
confidence: 99%
See 2 more Smart Citations
“…The study identified green purchasing behaviour of customers is more in developed countries than in developing countries. Lo and Leung (2000) identified the increasing environmental awareness of young customers. Eltayeb and Zailani (2010) identified consumer pressure as an important driver in reverse logistics.…”
Section: Review On Gscm Enablersmentioning
confidence: 99%